Beneficial effects of early treatment of infantile hemangiomas with a long‐pulse Alexandrite laser. Issue 3 (6th January 2014) - Su, Wenting; Ke, Youhui; Xue, Jixin
<x xml:space="preserve">Abstract</x> Background and Objective There is an increasing interest in treating vascular lesions with a long‐pulse Alexandrite laser. However, it is difficult to search information in the literature about infantile hemangiomas (IH) treated with long‐pulse Alexandrite laser. This article aims to determine whether 755 nm long‐pulse Alexandrite laser is effective and safe for early intervention of IH and provides some new data on this issue. Materials and Methods This is a retrospective study of 48 infants with IH treated with long‐pulse Alexandrite laser during a 1.5‐year period. Patients received a series of 1–7 treatment sessions with long‐pulse Alexandrite laser at settings of 3 milliseconds pulse duration, 6–8 mm spot, 45–70 J/cm2 fluences, and with dynamic cooling device (DCD) spray duration of 90 milliseconds and delay of 80 milliseconds, given at 4‐ to 6‐week intervals. Results This study demonstrated that IH responded favorably to the treatment of a long‐pulse Alexandrite laser while accompany with relatively few complications. The difference between the original untreated and post‐treatment scores of all IH and two subgroups were statistically significant, respectively (P < 0.01). The difference of the degree of improvement between the two subgroups was not significant (P > 0.05). It was observed that IH on the trunk and extremities improved more effectively and more quickly than those on the face, neck, and perineum. Besides, age at the first treatment, the sex of the patients and the presence of proliferation were not significantly correlated with the degree of improvement. Adverse effects were seen in 11 patients (22.91%): blistering (n = 9), marked edema and erosion without subsequent residual scarring (n = 1), and hypopigmentation (n = 1), which improved gradually with time. Fortunately, there was no incidence of scarring or ulceration in this case series of IH. Conclusions It was clinically effective and safe for early treatment of IH, including the thick/deep ones, with a long‐pulse Alexandrite laser, which indicated be able to reduce the possibility that the IH will reach its full size. In this way it can prevent several complications connected to the rapid proliferation of IH. Lasers Surg. Med. 46:173–179, 2014. © 2014 Wiley Periodicals, Inc.